Analisis Capaian Pembelajaran Bahasa Jerman dan Integrasi Nilai Profil Pelajar Pancasila dalam Kurikulum Merdeka di SMA - Alvidya Nisa Utami; Heny Subandiyah; Urip Zaenal Fanani; Syamsul Sodiq; Wisma Kurniawati (Universitas Muhammadiyah Mataram, 2025)
Abstract: Mastery of a foreign language is essential to prepare the younger generation for globalization. German, as a foreign language in Indonesian high schools, opens up academic and professional opportunities in German-speaking countries. This study aims to analyze the learning outcomes of German and explore the integration of Pancasila Learner Profile values in the Merdeka Curriculum. A descriptive qualitative approach is used by analyzing official documents such as the German Language Learning Outcomes (CP) and the Pancasila Learner Profile Guide. The results showed that German language learning can integrate values such as global diversity, critical reasoning, independence, and mutual cooperation through contextual and project-based approaches. The main challenges found were limited teacher training, lack of relevant teaching materials, and lack of implementation guidelines in schools. This research suggests improving teacher training and developing more contextualized teaching materials to support the integration of Pancasila values.Abstrak: Penguasaan bahasa asing sangat penting untuk mempersiapkan generasi muda menghadapi globalisasi. Bahasa Jerman, sebagai bahasa asing di SMA Indonesia, membuka peluang akademik dan profesional di negara-negara berbahasa Jerman. Penelitian ini bertujuan untuk menganalisis capaian pembelajaran Bahasa Jerman dan mengeksplorasi integrasi nilai-nilai Profil Pelajar Pancasila dalam Kurikulum Merdeka. Pendekatan deskriptif kualitatif digunakan dengan menganalisis dokumen resmi seperti Capaian Pembelajaran (CP) Bahasa Jerman dan Panduan Profil Pelajar Pancasila. Hasil penelitian menunjukkan bahwa pembelajaran Bahasa Jerman dapat mengintegrasikan nilai-nilai seperti berkebinekaan global, bernalar kritis, mandiri, dan gotong royong melalui pendekatan kontekstual dan berbasis proyek. Tantangan utama yang ditemukan adalah keterbatasan pelatihan guru, kurangnya bahan ajar yang relevan, dan minimnya panduan implementasi di sekolah. Penelitian ini menyarankan peningkatan pelatihan guru dan pengembangan bahan ajar yang lebih kontekstual dalam mendukung integrasi nilai-nilai Pancasila.